Prevalence of frailty and prediction of mortality in Chinese cancer patients using a frailty index‐based clinical algorithm—A multicentre study. (28th July 2021) - Jin, Xi; Ren, Yue; Shao, Li; Guo, Zengqing; Wang, Chang; He, Ying; Zhou, Lan; Cong, Minghua; Ma, Hu; Wang, Wei; Zhou, Chunling; Feng, Yongdong; et al.
Abstract: Purpose: To investigate the frailty status in Chinese cancer patients through establishing a novel prediction algorithm. Methods: The percentage of frailty in various age groups, locations, and tumor types in Chinese cancer patients was investigated. The prediction capacity of frailty on mortality of Chinese cancer patients was analysed by the frailty index composing of routine laboratory data (FI‐LAB) accessible from a blood test and calculated as the ratio of abnormal factors to 22 total variables. The establishment of a novel algorithm, MCP (mortality of cancer patients), to predict the 5‐year mortality in Chinese cancer patients was accomplished and the algorithm's prediction capacity was tested in the training and validation sets using receiver operating characteristic (ROC) analysis. Results: We found that the risk of death in cancer patients can be successfully identified through FI‐LAB. The univariable and multivariable Cox regression were used to evaluate the effect of frailty on death. In the 5‐year follow‐up, 20.6% of the 2959 participants (age = 55.8 ± 11.7 years; 43.5% female) died, while the mean FI‐LAB score in baseline was 0.23 (standard deviation = 0.13; range = 0–0.73). Frailty (after adjusting for gender, age, and other confounders) directly correlated with an increased risk of death, hazard ratio of 12.67 (95% confidence interval [CI]: 7.19, 22.31), compared to those without frailty. In addition, the MCP algorithm (MCP) = 3.678 × FI‐LAB + 1.575 × sex + 1.779 × first tumor node metastasis staging, presented an area under the ROC (AUC) of 0.691 (95% CI: 0.656–0.726) and 0.648 (95% CI: 0.613–0.684) in the training and validation sets, respectively. Conclusion: Frailty as defined by FI‐LAB was common and indicated a significant death risk in cancer patients. Our novel developed algorithm MCP had a passable prediction capacity on 5‐year MCP. Abstract : To investigate the frailty status in Chinese cancer patients through establishing a novel prediction algorithm. Frailty as defined by FI‐LAB (frailty index composing of routine laboratory data) was common and indicated a significant death risk in cancer patients. Our novel developed algorithm mortality of cancer patients had a passable prediction capacity on 5‐year mortality of cancer patients.